2008
DOI: 10.1634/theoncologist.2008-0093
|View full text |Cite
|
Sign up to set email alerts
|

Good Response to Gefitinib in Lung Adenocarcinoma of Complex Epidermal Growth Factor Receptor (EGFR) Mutations with the Classical Mutation Pattern

Abstract: Background. Epidermal growth factor receptor (EGFR) mutations are usually detected in lung adenocarcinoma and are associated with a response to EGFR tyrosine kinase inhibitors (TKIs). However, not all EGFR mutations have similarly high clinical response rates. This study aimed to investigate the clinical characteristics and response to gefitinib in lung adenocarcinoma patients with complex EGFR mutations.Materials and Methods. Three hundred thirty-nine specimens of lung adenocarcinoma from patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 54 publications
8
72
0
Order By: Relevance
“…Recently, it was found that EGFR mutation was a sensitive marker of NSCLC to EGFR TKI drugs, while KRAS mutation was a resistant one [22,23]. Considering the incidence of gene mutations including EGFR and KRAS in NSCLC varied regionally and racially, we detected EGFR and KRAS mutations in 157 NSCLC patients from mainland China, and found that the mutation frequencies of EGFR and KRAS were both similar to reports from other East Asia areas, such as Taiwan China, Japan and Korea [19,[24][25][26][27][28]. Comparing to western countries, the mutation frequency of EGFR was higher, while that of KRAS was lower in the East Asia areas [20,29,30].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, it was found that EGFR mutation was a sensitive marker of NSCLC to EGFR TKI drugs, while KRAS mutation was a resistant one [22,23]. Considering the incidence of gene mutations including EGFR and KRAS in NSCLC varied regionally and racially, we detected EGFR and KRAS mutations in 157 NSCLC patients from mainland China, and found that the mutation frequencies of EGFR and KRAS were both similar to reports from other East Asia areas, such as Taiwan China, Japan and Korea [19,[24][25][26][27][28]. Comparing to western countries, the mutation frequency of EGFR was higher, while that of KRAS was lower in the East Asia areas [20,29,30].…”
Section: Discussionmentioning
confidence: 57%
“…However, it is still unclear if the two type mutations in EGFR have different clinicopathological characteristics and clinical significance. It was noticed that patients with EGFR mutation in exon 19 had higher sensitive rates to TKI drugs and increased survival rates after treatment with TKI drugs in contrast to those with exon 21 mutations [11,[13][14][15][16][17][18], while some research groups didn't think so [19]. Shigematsu et al from Japan even thought patients with EGFR mutations of exon 21 exhibited an increase in survival if they had not received any form of chemotherapy including TKI drugs when compared to those with mutations of exon 19 [2].…”
mentioning
confidence: 99%
“…EGFR overexpression is also associated with poor prognosis. 33,63 Solid pattern has more ERCC1 expression than acinar and this aspect is very important because ERCC1 repairs DNA and confers resistance to some drugs.…”
Section: Solid Patternmentioning
confidence: 99%
“…25---31 EGFR and HER2 play a central role in tumorigenesis. 32,33 Targeting those receptors provides a unique approach for treating EGFR/HER2 expressing cancers. 34,35 The most common alteration of HER2 is overexpression/amplification; mutations are less frequent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation